2005
DOI: 10.1111/j.1651-2227.2005.tb01947.x
|View full text |Cite
|
Sign up to set email alerts
|

Leisure activities in adolescents with headache

Abstract: Aim: To investigate the association between different types of headache and leisure activities in 13‐y‐old schoolchildren. Methods: A population‐based, cross‐sectional study was performed through face‐to‐face interviews with age‐matched cohorts with headache and asymptomatic controls. The present study comprised 59 children with migraine, 65 with episodic tension‐type headache (TTHA) and 59 headache‐free controls. In the interview, besides questions concerning headache, the children were asked open and structu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
38
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(41 citation statements)
references
References 29 publications
3
38
0
Order By: Relevance
“…At the end of the 1980s, computer use at home or school was rare, but at the beginning of the 2000s, 93% of adolescents used computers, 54% daily. 18 According to our recent study, 19 children with migraine or with tension-type headache used computers more than those without headache. We also found that 1 more day of computer usage in a week increased the odds of belonging to the migraine or tension-type headache groups by 20% and 30%, respectively, compared with children without headache.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…At the end of the 1980s, computer use at home or school was rare, but at the beginning of the 2000s, 93% of adolescents used computers, 54% daily. 18 According to our recent study, 19 children with migraine or with tension-type headache used computers more than those without headache. We also found that 1 more day of computer usage in a week increased the odds of belonging to the migraine or tension-type headache groups by 20% and 30%, respectively, compared with children without headache.…”
Section: Discussionmentioning
confidence: 97%
“…We also found that 1 more day of computer usage in a week increased the odds of belonging to the migraine or tension-type headache groups by 20% and 30%, respectively, compared with children without headache. 19 Headache can be caused by tense neck muscles as a result of recurrent, monotonous, and static working postures at a computer. In addition, the flashing lights of computers may provoke migraine in children.…”
Section: Discussionmentioning
confidence: 99%
“…Xavier et al 18 state that adolescents abusively using electronic devices have higher chances (OR=1.52) of having headache. The literature also states that overload of visual system and maintenance of inadequate postures for long periods are reflected in headache reports by adolescents 2,9 . Notwithstanding our results being in agreement with most current literature and presenting statistical and social relevance, the study was limited by the fact of generalizing results for students of a public school and extending them to private school students.…”
Section: Discussionmentioning
confidence: 99%
“…Due to easy access to electronic devices more time is spent with them and, as a consequence, negative impact on adolescents' health have been reported in the literature, such as sleep changes, tiredness, anxiety, depression, overweight, de-ORIGINAL ARTICLE DOI 10.5935/1806-0013.20150049 creased levels of physical activities, decreased concentration, musculoskeletal pain, stress and headache [3][4][5][6][7] . Headache, pointed as an increasing problem among children and adolescents and which is possibly related to changes in lifestyle and stress-related factors 8 , has been highlighted by some studies as a major complaint among adolescents due to the excessive use of electronic devices 6,9 . Recently, Brindova et al 1 have observed that adolescents referring watching TV for more than three hours per day have higher chances of reporting physical and psychological complaints, including headache.…”
Section: Introductionmentioning
confidence: 99%
“…Children with TTH have been associated with more frequent use of computers than healthy controls [35]. Straker et al [36] examined posture and muscle activity in young children with a mean age 5.6 years who were using either a tablet, desktop or paper.…”
Section: Posture Muscle Activity and The Use Of Electronic Devices Bmentioning
confidence: 99%